Monitoring participatory land use planning for better impact on landscapes and livelihoods: case studies in Nambor, Sobchia and Pakhok villages, Phonxay district, Luang Prabang province - Bouahom, B.; Bourgoin, Jeremy; Lestrelin, Guillaume; Castella, J.C. (2011)
Since the early 1990s, a Land Use Planning and Land Allocation (LUP/LA) Programme has been implemented throughout Laos in order to increase land tenure security, to stabilize shifting cultivation, increase forest cover and to avoid the negative impacts of deforestation as to protect the environment in a country that is still rich in forest resources. LUP/ LA implementation consists in land use planning, forest and land classification, and land allocation - through the provision of temporary land use certificates to individual household. According to various studies, LUP/LA implementation in Laos did not always encounter the success predicted by the Laotian government. During the decade from 1995 to 2005 LUP/ LA continued in most provinces, after which there was a slowdown of activity because it had been undertaken in the majority of accessible villages and there was a marked decrease in funds made available by the government of Laos for LUP/LA in more remote villages. In 2008, a technical advisory group was formed to develop new approaches and procedures and prepare an improved manual on Participatory Land Use Planning (PLUP). The new approach described in this manual concentrates on participatory land use zoning at the village and village cluster levels by using modern technologies such as GPS and GIS. At this period of transition between LUP/LA and PLUP, our main research objective was to assess the impact of land policy on livelihoods in the uplands of Laos, in particular, to analyze the diversity and the outcomes of LUP/LA implementation. Three villages of Phonxay district of Luangphabang province were selected as study sites. In the two former villages, LUP/LA has been implemented at different times and through different approaches. In the latter village, LUP/LA had not been implemented but the village had been selected for a first experimentation of the new PLUP approach. The research found that LUP/LA did not influence much in term of livelihood. The land use planning process did not restrict the village agricultural land. Basically, the land use planning did officialize the distribution of the different land uses that existed previously.The land declared by each family during land allocation depended mainly on their reluctance to pay taxes and on the priority given to plots close to the road for registration. As a consequence the remote plots, where shifting cultivation is still practiced, were often left unregistered. The evolution of village land use planning and practices during the past decade from early LUP/LA to pilot implementation of PLUP has been accompanied by a slight increase in local participation.